Development of The Banna Game Integrated ContextualLearning Instruction on Ecosystem Materials in Junior High School - Retno Dwi Purwaningsih; Suratno Suratno; Mochammad Iqbal (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
The implementation of the curriculum 2013 revised edition was reinstated by the government in 2016 that made all elements of the school especially teachers should adapt the learning tools used in the teaching system. Learning tools include syllabus, RPP, Textbooks, LKS, and learning media. Science learning according to the 2013 curriculum is done contextually for example by applying environment based learning by maximizing the enviromental potential that exists in the area around the school. Ecosystem is a material that must be done contextually. One of methode for teachers to improve their learning motivation and student learning outcomes is by developing a The Banna Game integrated contextual learning instruction. Game The Banna is an educational game themed Baluran National Park. This study aims to develop The Banna Game integrated contextual learning instruction on the subject of Ecosystems on Learning Motivation and Student Cognitive Learning Outcomes at SMPN 1 Asembagus Situbondo. This research is a developmental research using ASSURE model. The developmental research is carried out in Biology Education Study Program which involves several validators, Baluran National Park experts, application experts, learning device experts, learning media experts and materials experts. Test validity based on the validation assessment of the five validators to test the feasibility of the product to be used in the school. Validity test results obtained are TNB Expert 92.1%, Media Experts 89.70%, Expert Learning Tool 71.875%, Media Experts 77.083% and Expert Content 73%. Based on it shows that the level of validity of learning devices obtain valid categories and can be used in learning activities in the school.